Grey wolf assisted dragonfly-based weighted rule generation for predicting heart disease and breast cancer. (July 2021) - Moturi, Sireesha; Rao, S.N.Tirumala; Vemuru, Srikanth
Highlights: Exploits the advanced New levy Update based Dragonfly Algorithm (NL-DA). Propose a new disease prediction model with advanced classification techniques. New disease prediction model comprises three phases. They are Coalesce rule generation, feature extraction, and classification. Performance of proposed disease prediction model is better than conventional models. Abstract: Disease prediction plays a significant role in the life of people, as predicting the threat of diseases is necessary for citizens to live life in a healthy manner. The current development of data mining schemes has offered several systems that concern on disease prediction. Even though the disease prediction system includes more advantages, there are still many challenges that might limit its realistic use, such as the efficiency of prediction and information protection. This paper intends to develop an improved disease prediction model, which includes three phases: Weighted Coalesce rule generation, Optimized feature extraction, and Classification. At first, Coalesce rule generation is carried out after data transformation that involves normalization and sequential labeling. Here, rule generation is done based on the weights (priority level) assigned for each attribute by the expert. The support of each rule is multiplied with the proposed weighted function, and the resultant weighted support is compared with the minimum support for selecting the rules. Further, the obtained rule is subject to the optimal feature selection process. The hybrid classifiers that merge Support Vector Machine (SVM), and Deep Belief Network (DBN) takes the role of classification, which characterizes whether the patient is affected with the disease or not. In fact, the optimized feature selection process depends on a new hybrid optimization algorithm by linking the Grey Wolf Optimization (GWO) with Dragonfly Algorithm (DA) and hence, the presented model is termed as Grey Wolf Levy Updated-DA (GWU-DA). Here, the heart disease and breast cancer data are taken, where the efficiency of the proposed model is validated by comparing over the state-of-the-art models. From the analysis, the proposed GWU-DA model for accuracy is 65.98 %, 53.61 %, 42.27 %, 35.05 %, 34.02 %, 11.34 %, 13.4 %, 10.31 %, 9.28 % and 9.89 % better than CBA + CPAR, MKL + ANFIS, RF + EA, WCBA, IQR + KNN + PSO, NL-DA + SVM + DBN, AWFS-RA, HCS-RFRS, ADS-SM-DNN and OSSVM-HGSA models at 60th learning percentage.